Licencias obligatorias para exportación: Operacionalización en el orden jurídico argentino - Valentina Delich (South Centre, 2024)
In 2017, the amendment to the Agreement on Trade-Related Intellectual Property Rights (TRIPS) entered into force, whereby Article 31bis was included in its text. This provision allows compulsory licensing for exports to third countries with no or insufficient local production capacity. The aim is to alleviate the difficulties faced by countries without drug production infrastructure so that they can make effective use of compulsory licensing and thus strengthen access to medicines at a lower price. Argentina is a country that has drug production infrastructure and could potentially become an efficient exporter. This paper explores the possible implementation of art. 31 bis in Argentina's legislation, proposing to incorporate into the national patent law the concept of humanitarian compulsory licensing.
Keywords: 300; Access to Medicines; Argentina; Article 31bis; Compulsory Licenses; Compulsory Licensing; Export; Intellectual Property; Local Production; Patent; Patent Law; Public Health; TRIPS; TRIPS Agreement; TRIPS Flexibilities